Inventory and Utilization Aren (A. pinnata) by Forest Communities Widely (Study Case: Sihombu Village, Tarabintang District, Humbang Hasundutan Regency) - Rionaldo Damanik; Irawati Azhar; Riswan Riswan (Program studi Kehutanan USU, 2014)
Aren (A. pinnata) are included in the arecaceae (areca nut) and are included in the inclosed seed plants (angiospermae). Aren is a forest plant that has many benefits but is not yet used by forest communities widely. The purpose of this study has to elevate the potential, distribution and utilization of aren. This research was using compartment sampling with compartment strip technique. The result showed that optimal growth of aren in elevate 550-560 mdpl and the utilization of aren such as, sugar palm juice, palm wine, palm fiber, leaf adnd steam. The sugar processing plants by the human in this area is steal simple and production potential processing has not been abel to be treated optimally.Keywords: Aren, potential, utilization, production.